Effects induced through the use of physical and motor tests in volleyball - Alminni, C.; Altavilla, G.; Scurati, R.; D'Elia, F. (Journal of Human Sport & Exercise, 2019)
The purpose of the study was to analyse and evaluate the jumping ability and the fundamental technical of the float serve in volleyball in 3 areas of the opposing camp (1-6-5), in order to evaluate the effectiveness of a working method. The study was performed on a sample of 12 male volleyball players (Category: Under 20). Data were collected in two periods (September and October), subjecting the players to intensive technical and physical work. At the beginning of the training period anthropometrics data (weight, height, BMI, reach to one hand) and the values at the vertec jump test were collected. Each player carried out 90 float services (3 series of 30 float serves, respectively to specific areas of the opponent's field 1-6-5) to check out if there is continuity of precision towards the three zones or if there is a significant difference. The results show, after four weeks of intensive training, an improvement in jumping ability at the Vertec test. It is hypothesized a not significant difference in the performance by the group of players, in terms of precision, towards the three opposing areas and a positive difference in pre-training (September) and post-training (October) performances. The monitoring of the training process will allow to estimate the effects induced through the use of physical and motor tests, allowing the coaches to design and choose the methodology and the appropriate training load, for an effective performance.